(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article reveals that the influence and significance of literature on social and spiritual life. Information is also provided about the unique features of the short story genre and its place in literature. In Uzbek and English story writing with the artistic style of “sarcasm” are compared and analyzed. Among them, the similarities and differences between the works of Abdulla Khahhor, a unique master of the Uzbek short story genre, and the famous English writer Katherine Mansfield will be highlighted. As an example, one of the popular works of two authors was taken, its content and main ideas were compared.